2022
DOI: 10.1029/2022gl097989
|View full text |Cite
|
Sign up to set email alerts
|

One‐Dimensional gcPIC‐δf Simulation of Hooked Chorus Waves in the Earth’s Inner Magnetosphere

Abstract: As one of the most commonly observed plasma waves in the Earth's inner magnetosphere, whistler-mode waves play an important role in governing electron dynamics therein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…There are six major rising tone elements shown in the interval. These repetitive emissions of chorus waves are considered to be related to the injection of energetic electrons from the magnetotail (Chen, Lu, et al., 2022; Gao et al., 2022; Lu et al., 2021). All of the chorus risers began close to f0.17em=0.17em0.5fce $f\,=\,\sim 0.5{f}_{\text{ce}}$ (∼2,400 Hz) and rose to 0.62fce $\sim 0.62{f}_{\text{ce}}$ (∼3,000 Hz).…”
Section: Observational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six major rising tone elements shown in the interval. These repetitive emissions of chorus waves are considered to be related to the injection of energetic electrons from the magnetotail (Chen, Lu, et al., 2022; Gao et al., 2022; Lu et al., 2021). All of the chorus risers began close to f0.17em=0.17em0.5fce $f\,=\,\sim 0.5{f}_{\text{ce}}$ (∼2,400 Hz) and rose to 0.62fce $\sim 0.62{f}_{\text{ce}}$ (∼3,000 Hz).…”
Section: Observational Resultsmentioning
confidence: 99%
“…Chen et al. (2021, 2022a) have suggested that the Landau accelerated low energy electron beam causes further cyclotron damping of the 0.5fce $\sim 0.5{f}_{\text{ce}}$ waves at the equator, so both Landau and cyclotron damping are involved.…”
Section: Introductionmentioning
confidence: 99%
“…They can appear as rising tones, falling tones, and hiss‐like emissions in dynamic spectra (Gao et al., 2014; Li et al., 2012). In general, the chorus waves with distinct elements are repetitive (Chen, Lu, et al., 2022; Lu et al., 2021; Shue et al., 2015). There is usually a power gap around 0.5 fce ${f}_{ce}$ (where fce ${f}_{ce}$ is the electron gyrofrequency at the equator), naturally forming lower (0.1–0.5 fce ${f}_{ce}$) and upper (0.5–0.8 fce ${f}_{ce}$) band chorus (Burtis & Helliwell, 1969; Chen, Gao, et al., 2022; Chen et al., 2021; Gao et al., 2017, 2019; Tsurutani & Smith, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…They can not only efficiently scatter low‐energy (0.1–30 keV) electrons into the loss cone and cause diffuse aurora in the upper atmosphere (Kasahara et al., 2018; Ni et al., 2008), but also accelerate seed electrons (∼100 keV) to relativistic energies (∼MeV), refilling the outer radiation belt during geoactive storms (Horne et al., 2003; Summers et al., 1998; Thorne et al., 2013). Besides the typical exhibition of the frequency chirping (Burtis & Helliwell, 1969; H. Chen et al., 2022; X. L. Gao et al., 2014; Ke et al., 2017, 2020; Lu et al., 2019; Omura et al., 2009; Tsurutani & Smith, 1974, 1977) and repetitive emissions (H. Chen et al., 2022; Hikishima et al., 2010; Lu et al., 2021; Tsurutani et al., 2013), another notable characteristic of whistler‐mode waves in the Earth's magnetosphere is the power gap around 0.5Ω e (where Ω e is the equatorial electron gyrofrequency), which visually separates the spectrum into a lower band (0.1–0.5Ω e ) and an upper band (0.5–0.8Ω e ) (Fu et al., 2014; X. Gao et al., 2019; W. Li et al., 2011; Tsurutani & Smith, 1974).…”
Section: Introductionmentioning
confidence: 99%